Orbital Analysis of Carbon‐13 Chemical Shift Tensors Reveals Patterns to Distinguish Fischer and Schrock Carbenes. (7th June 2017) - Yamamoto, Keishi; Gordon, Christopher P.; Liao, Wei‐Chih; Copéret, Christophe; Raynaud, Christophe; Eisenstein, Odile
Abstract: Fischer and Schrock carbenes display highly deshielded carbon chemical shifts (>250 ppm), in particular Fischer carbenes (>300 ppm). Orbital analysis of the principal components of the chemical shift tensors determined by solid‐state NMR spectroscopy and calculated by a 2‐component DFT method shows specific patterns that act as fingerprints for each type of complex. The calculations highlight the role of the paramagnetic term in the shielding tensor especially in the two most deshielded components (σ11 and σ22 ). The paramagnetic term of σ11 is dominated by coupling σ(M=C) with π*(M=C) through the angular momentum operator perpendicular to the σ and π M=C bonds. The highly deshielded carbon of Fischer carbenes results from the particularly low‐lying π*(M=C) associated with the CO ligand. A contribution of the coupling of π(M=C) with σ*(M=C) is found for Schrock and Ru‐based carbenes, indicating similarities between them, despite their different electronic configurations (d 0 vs. d 6 ).